Analisis Pengaruh Dana Alokasi Umum (DAU) dan Pendapatan Asli Daerah (PAD) terhadap Prediksi Belanja Daerah (Studi Empirik di Wilayah Propinsi Jawa Tengah Dan DIY) - Kesit Bambang Prakosa (Accounting Department, Faculty of Business and Economics, Universitas Islam Indonesia, 2004)
The aim of this research is to analyse DAU and PAD’s influence and their ability to predict district’s spending in Indonesia. The samples of this research are taken from the realisation of budget of Kabupaten/Kota within the Province of Central Java and DIY. The results show that DAU and PAD partially as well as collectively have indeed influenced the realisation of budget and district’s taxes. Furthermore, we might conclude from the results that there has been a flypaper effect which is showed by the DAU which has higher ability to predict district’s spending than the PAD.Keywords: Dana Alokasi Umum (DAU), Pendapatan Asli Daerah (PAD), Pajak Daerah (PJD), Belanja Daerah (BJD) and flypaper effect.